Escherichia coli O127 group 4 capsule proteins assemble at the outer membrane. - Matthew R Larson; Kassia Biddle; Adam Gorman; Sarah Boutom; Ilan Rosenshine; Mark A Saper (PLoS ONE)
Enteropathogenic Escherichia coli O127 is encapsulated by a protective layer of polysaccharide made of the same strain specific O-antigen as the serotype lipopolysaccharide. Seven genes encoding capsule export functions comprise the group 4 capsule (gfc) operon. Genes gfcE, etk and etp encode homologs of the group 1 capsule secretion system but the upstream gfcABCD genes encode unknown functions specific to group 4 capsule export. We have developed an expression system for the large-scale production of the outer membrane protein GfcD. Contrary to annotations, we find that GfcD is a non-acylated integral membrane protein. Circular dichroism spectroscopy, light-scattering data, and the HHomp server suggested that GfcD is a monomeric β-barrel with 26 β-strands and an internal globular domain. We identified a set of novel protein-protein interactions between GfcB, GfcC, and GfcD, both in vivo and in vitro, and quantified the binding properties with isothermal calorimetry and biolayer interferometry. GfcC and GfcB form a high-affinity heterodimer with a KD near 100 nM. This heterodimer binds to GfcD (KD = 28 μM) significantly better than either GfcB or GfcC alone. These gfc proteins may form a complex at the outer membrane for group 4 capsule secretion or for a yet unknown function.